Proposed Framework Of A Knowledge-Based Performance Management System (KBPMS) For Furniture Smes: A Case Study Of Cv Mulya Pratama Putra - Ramadhan, Dimas Rizki M.; Wibisono, Dermawan (Amkop Management Accounting Review (AMAR), 2025)
A Knowledge-Based Performance Management System (KBPMS) is designed for performance management effectiveness in CV Mulya Pratama Putra, an Indonesian SME that specializes in wooden and rattan furniture exports. The SME witnessed declining operation and financial performance. The KBPMS uses a combination of external analysis methods including PESTEL and Porter’s Five Forces analysis and internal capability analysis methods that include VRIO and benchmarking. To prioritize improvements, an AHP method will be adopted. Analysis and findings have shown that there are major gaps in performance with regards to financial, customer, internal process, and resource capabilities. The AHP analysis also confirms Process Variables and Operational Quality factors as the main priorities. A KBPMS model will enable a proper and systematic determination of indicators and preparation of an improvement plan. KBPMS will enable an Indonesian SME like Mulya Pratama Putra to make more knowledge-driven decisions and improve its global competitiveness and ability to export.